Sistema de intermédio do especialista e monitoramento da saúde com recomendação personalizada de conteúdos - Sousa Neto, Ademar França de (2019)
Chronic diseases impose on the wearer limitations your health condition. Therefore, learning more about the disease helps improve the quality of life. Thus, the chronic disease Diabetes is a metabolic syndrome of origin related to the supply of insulin by the pancreas. The problem occurs when there is total or partial insufficiency in the supply of insulin or when the pancreas does not have the capacity to adequately exercise its function. In any situation, there is an increase in the level of glucose in the blood. This is a disease that is growing fastest today, thus requiring software that can meet both patient and health specialist demand. Thus, in order to facilitate the life of those who suffer from this condition, a tool is proposed that involves semiautomatic monitoring of health data and automatic calculation of the amount of insulin needed to control glucose. The tool also aims to assist both the patient and the specialist in managing the disease and provide means to promote informal learning through personalized recommendation of content taking into account health data. This work presents an Intermediate System of the Expert with recommendation of personalized contents for the target user, seeking to favor informal learning in health